Global burden of non-communicable chronic diseases associated with a diet low in fruits from 1990 to 2019 - Pan, Shijie; Lin, Zhihan; Yao, Teng; Guo, Xiaoli; Xu, Tongtong; Sheng, Xinyan; Song, Xi; Chen, Zuhai; Wei, Wanting; Yan, Yizhong; Hu, Yunhua (Frontiers in Nutrition, 2023)
The aim of this study was to assess the global burden of disease from noncommunicable chronic diseases (NCD) due to diet low in fruits from 1990 to 2019.Based on data from the Global Burden of Disease (GBD) 2019, the global burden of disease due to diet low in fruits was analyzed for each country or region, disaggregated by disease type, age, sex, and year. The number of deaths and disability-adjusted life years (DALYs), population attributable fraction (PAF), age-standardized mortality rate (ASMR) and age-standardized DALY rate (ASDR) were calculated, and the average annual percentage change (AAPC) was calculated to describe trends in ASMR and ASDR from 1990 to 2019.Results: From 1990-2019, the number of deaths and DALYs due to diet low in fruits increased by 31.5% and 27.4%, respectively. Among the tertiary diseases, ischemic heart disease, stroke, and diabetes and kidney disease were the top three contributors to the global increase in deaths and DALYs. However, both ASMR and ASDR showed a decreasing trend. The fastest decline in ASMR and ASDR was in stroke, with AAPC of -2.13 (95% CI: -2.22, -2.05, P<0.05) and -0.56 (95% CI: -0.62, -0.51, P<0.05), respectively. For GBD regions, high PAF occurred mainly in South Asia, This is a provisional file, not the final typeset article Oceania, and sub-Saharan Africa. Age-specific PAF for stroke and ischemic heart disease death attributable to diet low in fruits was significantly negatively associated with age. Diet low in fruits related ASMR and ASDR showed an M-shaped relationship with the socio-demographic index (SDI), but with an overall decreasing trend.The number of deaths and DALYs due to diet low in fruits continues to increase. Therefore, early nutritional interventions should be implemented by the relevant authorities to reduce the burden of diseases caused by diet low in fruits.